KAJIAN ILMIAH MAKROSKOPI, MIKROSKOPI DAN KIMIAWI RIMPANG TEMU PUTIH (Curcuma zedoaria (Berg.) Roscoe) - , HENDRI MARINDA SARI; , Dra. Sri Mulyani, SU., Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
-